Real-World Impact of the Accelerate PhenoTest BC Kit on Patients With Bloodstream Infections in the Improving Outcomes and Antimicrobial Stewardship Study: A Quasiexperimental Multicenter Study . (27th October 2021) - Bhalodi, Amira A; MacVane, Shawn H; Ford, Bradley; Ince, Dilek; Kinn, Patrick M; Percival, Kelly M; Bremmer, Derek N; Carr, Dustin R; Walsh, Thomas L; Bhatti, Micah M; Shelburne, Samuel A; Humphries, Romney M; et al.
Abstract: Background: Bloodstream infections (BSIs) are a leading cause of morbidity and mortality. The Improving Outcomes and Antimicrobial Stewardship study seeks to evaluate the impact of the Accelerate PhenoTest BC Kit (AXDX) on antimicrobial use and clinical outcomes in BSIs. Methods: This multicenter, quasiexperimental study compared clinical and antimicrobial stewardship metrics, prior to and after implementation of AXDX, to evaluate the impact this technology has on patients with BSIs. Laboratory and clinical data from hospitalized patients with BSIs (excluding contaminants) were compared between 2 arms, 1 that underwent testing on AXDX (post-AXDX) and 1 that underwent alternative organism identification and susceptibility testing (pre-AXDX). The primary outcomes were time to optimal therapy (TTOT) and 30-day mortality. Results: A total of 854 patients with BSIs (435 pre-AXDX, 419 post-AXDX) were included. Median TTOT was 17.2 hours shorter in the post-AXDX arm (23.7 hours) compared with the pre-AXDX arm (40.9 hours; P <.0001). Compared with pre-AXDX, median time to first antimicrobial modification (24.2 vs 13.9 hours; P <.0001) and first antimicrobial deescalation (36.0 vs 27.2 hours; P =.0004) were shorter in the post-AXDX arm. Mortality (8.7% pre-AXDX vs 6.0% post-AXDX), length of stay (7.0 pre-AXDX vs 6.5 days post-AXDX), and adverse drug events were not significantly different between arms. Length of stay was shorter in the post-AXDX arm (5.4 vs 6.4 days; P =.03) among patients with gram-negative bacteremia. Conclusions: For BSIs, use of AXDX was associated with significant decreases in TTOT, first antimicrobial modification, and time to antimicrobial deescalation. Abstract : In this real-world, quasiexperimental, multicenter study, we found that use of the Accelerate PhenoTest BC Kit testing method for patients with bloodstream infections shortened the time to optimal therapy and time to antimicrobial deescalation due to faster antimicrobial modifications.